Variasi Posisi Kondilus Mandibula Pada Pasien Maloklusi Kelas I Angle Dilihat Dari Radiografi Panoramik - Resti Iswani; kornialia kornialia; Karlyn Arnelisa (Universitas Baiturrahmah, 2022)
Introduction: Mandibular condyle is the temporomandibular joint component that is most active and mainly receives loads when the mandible is functioning. The load received by the condyle can cause Temporomandibular Disorder (TMD). One of the etiology of TMD is the non-harmonious occlusion, as can be seen in Class I Angle Malocclusion which can affect the change in the condyle position from the center of the mandibular fossa. Panoramic radiographs examination can aid in the diagnosis of the condyle and measure the position in the condylar space. The purpose of this study was to determine the symmetries and the variations in positions of the mandibular condyles in Malocclusion Class I Angle patients and to determine their causes. Methods: This type of research is a quantitative, observational descriptive method, with a purposive sampling method. Samples were taken using the purposive sampling method from secondary data from patients with malocclusion who visit independent practice orthodontists from August 2017 - March 2020. Results: In the patient with Class I Angle Malocclusion, there were 14 (70%) with an asymmetric mandibular condyle position, 16 patients (80%) with right condyles anterior to the central fossa, and 15 patient (75%) with left condyles anterior to central fossa. Conclusion: Pathological occlusion in Class I malocclusion could also affect the mandibular condyle.